Regional Trade and Financial Mobilisation as Preconditions for Economic Growth: The Case of ECOWAS - JACKSON, Emerson Abraham; TAMUKE, Edmund Chijeh; JALLOH, Talatu (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024, 2024)
This empirical study delves into the Economic Community of West African States (ECOWAS) and its impact on economic growth through regional trade and financial mobilisation amongst its 15 member states. Through examination of data from 2005 to 2022, the study took into consideration a blend of static and dynamic panel data econometrics to explore nuances of trade openness, foreign direct investment (FDI), Domestic Credit to the Private Sector (CPS), and other factors influencing Real Gross Domestic Product (RGDP). The findings highlight a positive relationship between trade openness, FDI and economic growth, emphasising the importance of regional trade integration and foreign investment in driving economic development. Conversely, domestic credit shows a negative association with economic growth, thereby indicating the need for cautious assessment of credit allocation and financial sector efficiency. The study also reveals the important role of institutional quality in fostering economic growth, thereby recommending for policy reforms that strengthen governance frameworks and promote institutional resilience. Astonishingly, the analysis shows no significant relationship between inflation, transportation infrastructure, and economic growth. Theses insights contribute to a clear understanding of the dynamics between regional trade, financial mobilisation, and economic development within ECOWAS, thereby offering valuable implications for policymakers, with the aim of enhancing economic growth and integration in the region .